Sharp increase of imported Plasmodium vivax malaria seen in migrants from Eritrea in Hamburg, Germany. (December 2016) - Roggelin, Louise; Tappe, Dennis; Noack, Bernd; Addo, Marylyn; Tannich, Egbert; Rothe, Camilla
Abstract Background Since 2014, a considerable increase inPlasmodium vivax malaria has been observed in Germany. The majority of cases was seen in Eritrean refugees. Methods All patients withP. vivax malaria admitted to the University Medical Centre Hamburg-Eppendorf Germany from 2011 until August 2015 were retrospectively identified by the hospital coding system and data was matched with records from the laboratory diagnostics unit of the Bernhard Nocht Institute for Tropical Medicine, Hamburg, Germany. Results Between May 2014 and August 2015, 37 cases were reported in newly-arrived Eritrean refugees at the University Medical Centre Hamburg-Eppendorf, Germany. Relapses occurred due to difficulties in procurement of primaquine. Conclusion Countries hosting Eritrean refugees need to be aware of vivax malaria occurring in this group and the risk of autochthonous cases due to local transmission by indigenous, vector competent Anopheles species.